AGING IN LIGNINOLYTIC FUNGI IN SPACE CONDITIONS: AGING IN LIGNINOLYTIC FUNGI IN SPACE CONDITIONS - Miteva-Staleva, Jeny; Kostadinova, Nedelina; Hubenov, Venelin (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
Aging is considered in the context of various abiotic stresses, such as water deficit, high temperature, salinity, cold, heavy metals, mechanical wounding, UV radiation, etc. It is well known that the extreme level of these factors can be reflected in sharply increased production of reactive oxygen species. Reactive oxygen species interact with cellular biomolecules, such as lipids, proteins and DNA and can play an important role in cell injury. At the same time, fungi are an appropriate model system in different research areas, including aging. Testing of ligninolytic fungi in space conditions is forthcoming. However, it is unknown how the conditions of microgravity would affect fungal cell aging and enzyme production. Determination of the long-term physiological responses and adaptation to the space environment is of great importance for fungal enzyme production as well.